2020
DOI: 10.2118/203822-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Nonionic Surfactant Foam for CO2 Mobility Control in a Heterogeneous Carbonate Reservoir

Abstract: Summary In this paper, we describe a laboratory investigation of a nonionic surfactant for carbon dioxide-(CO2-) foam mobility control in the East Seminole field, a heterogeneous carbonate reservoir in the Permian Basin of west Texas. A method of high-performance liquid chromatography-evaporativelight-scattering detector (HPLC-ELSD) was followed for characterizing the surfactant stability. The foam transport process was studied in the absence and the presence of East Seminole crude oil, with tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Once the wormhole had been formed, it significantly altered the pressure measurements, due to the increase in permeability along the path of the wormholes, especially at the entrance of the core where there was most damage. Similar problems have also been described by Gland et al 23 and Jian et al 27 It was observed that the most significant damage (as observed from the pressure traces) often occurred during the transition from one foam quality to another, i.e., when switching from a high CO 2 fraction to a high water fraction or vice versa. The reason for this is not known.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Once the wormhole had been formed, it significantly altered the pressure measurements, due to the increase in permeability along the path of the wormholes, especially at the entrance of the core where there was most damage. Similar problems have also been described by Gland et al 23 and Jian et al 27 It was observed that the most significant damage (as observed from the pressure traces) often occurred during the transition from one foam quality to another, i.e., when switching from a high CO 2 fraction to a high water fraction or vice versa. The reason for this is not known.…”
supporting
confidence: 81%
“…The oxygen scavenger used for all the core flood tests was 100 ppm of carbohydrazide, as there are known issues (possible gypsum formation) when using the sodium sulphite in a carbonate core. 27 Between five and seven pore volumes of the solution were injected at 1 mL/min (equivalent to 1.47 × 10 −5 m/s or 4.2 feet/day). The effluent was captured in the fraction collector with a sample size of 4 mL (∼0.1 PV) each.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the hydrophilic-lipophilic balance and length of an ethoxylated group [13], nonionic surfactants can have good solubility and stability in high-salinity water. However, nonionic surfactants showed low foaming ability, compared to ionic type surfactants [14][15][16][17]. Comparison made by Li et al [18] of three types of surfactant: nonionic, anionic and anionic-nonionic, showed that anionic-nonionic surfactant created foam with higher stabilized pressure during filtration tests and higher foam elasticity than others.…”
Section: Introductionmentioning
confidence: 99%